The Implementation of an Educational Management Information System to Strengthen Character Education in Senior High Schools - Riwayanto, Ari; Maryanto, Maryanto; Nurkolis, Nurkolis (Jurnal Ragam Pengabdian, 2026)
The advancement of digital technology has encouraged schools to utilize information systems not only for administrative efficiency but also to support educational quality and character development. This study examined the implementation of the Educational Management Information System (EMIS) in supporting character education at SMAN 1 Patean, Kendal Regency. A qualitative descriptive approach was employed using in-depth interviews, participant observation, and document analysis involving the principal, teachers, administrative staff, students, the school committee, and parents. Data credibility was ensured through source and method triangulation, while analysis followed the Miles and Huberman interactive model. The findings indicate that EMIS was systematically integrated into school management through planning, implementation, and evaluation. It enhanced academic administration, attendance, assessment, parent communication, and monitoring of students’ character development, thereby improving efficiency, transparency, and evidence-based decision-making. EMIS also functioned as a management control tool by providing accurate and integrated data for continuous improvement. The study concludes that EMIS is a strategic instrument for strengthening school governance and improving the effectiveness of character education, offering practical guidance for schools implementing digital education management systems.